Insights into Aurignacian daily life and camp organization: The open-air site of Régismont-le-Haut. (30th December 2018) - Anderson, Lars; Lejay, Mathieu; Brugal, Jean-Philip; Costamagno, Sandrine; Heckel, Claire; de Araujo Igreja, Marina; Pradeau, Jean-Victor; Salomon, Hélène; Sellami, Farid; Théry-Parisot, Isabelle; Barshay-Szmidt, Carolyn; Mensan, Romain; et al.
Abstract: Régismont-le-Haut, an Aurignacian open-air campsite, provides an occasion to investigate aspects of Aurignacian site variability that are rarely broached: (1) the relatively poorly known area connecting the Aquitaine and Mediterranean Basins, and (2) the high-resolution spatial organization of an Early Upper Palaeolithic campsite. While more difficult to integrate directly into chronological models of Aurignacian evolution, mostly derived from stratified rock-shelter and cave sites from the northern Aquitaine Basin, it is argued that studying open-air sites like Régismont-le-Haut can furnish detailed information that rock shelter/cave sites cannot, therefore providing critical building blocks and possible reading keys to help reconstruct prehistoric circulation systems and marry synchronic and diachronic perspectives on variability. A detailed description of the geomorphological and sedimentary context, as well as the differing materials and activities (lithic industry and use-wear, faunal remains, mineral colouring materials, personal ornamentation, limestone blocks, fireplaces) that occur on-site, is provided. A summary of activities occurring in two complementary loci ensues, followed by a preliminary spatial reading of one of the primary domestic units. The contemporaneity of the two loci is then treated, and the article finishes with a discussion regarding how Régismont-le-Haut fits both diachronically and synchronically within the Aurignacian.